College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 2 - Summary, Review, and Test - Test - Page 327: 18



Work Step by Step

(g-f)(x)=g(x)-f(x) (g-f)(x)=2x-6-(x$^2$-x-4) (g-f)(x)=2x-6-x$^2$+x+4 (g-f)(x)=-x$^2$+3x-2
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.